2020
DOI: 10.1038/s42003-020-01277-6
|View full text |Cite
|
Sign up to set email alerts
|

High frequency acoustic cell stimulation promotes exosome generation regulated by a calcium-dependent mechanism

Abstract: Exosomes are promising disease diagnostic markers and drug delivery vehicles, although their use in practice is limited by insufficient homogeneous quantities that can be produced. We reveal that exposing cells to high frequency acoustic irradiation stimulates their generation without detriment to cell viability by exploiting their innate membrane repair mechanism, wherein the enhanced recruitment of calcium ions from the extracellular milieu into the cells triggers an ESCRT pathway known to orchestrate exosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 76 publications
4
79
0
Order By: Relevance
“…Interestingly, the Ca 2+ ionophore was able to initiate significant EV production also in the absence of external Ca 2+ , probably by mobilization of internal sources. This observation suggests that the machinery itself that leads to physical formation of EVs depends strongly on Ca 2+ signaling independent from the source of Ca 2+ (36)(37)(38).…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, the Ca 2+ ionophore was able to initiate significant EV production also in the absence of external Ca 2+ , probably by mobilization of internal sources. This observation suggests that the machinery itself that leads to physical formation of EVs depends strongly on Ca 2+ signaling independent from the source of Ca 2+ (36)(37)(38).…”
Section: Discussionmentioning
confidence: 92%
“…Other mechanical forces have also been introduced to cells, such as acoustic vibration, to increase the EVs secretion (Figure 4(b)). 48 When a high-frequency acoustic vibration (10 MHz) was applied to cells using an electrical stimulating piezoelectric device, the EVs were produced significantly more (15 times) when compared to non-vibration conditions. The higher EVs production was reasoned to the increased influx of calcium ions.…”
Section: Quantity and Mass Production Of Evsmentioning
confidence: 97%
“…applying physicomechanical cues such as forces 35,[46][47][48] and other stimuli (e.g. electricity, thermal, photodynamic, radiative stress).…”
Section: Quantity and Mass Production Of Evsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have reported the relief of in ammation in skin tissues and infected organs in animal models [22]. The current focus of antiin ammatory studies using MSC-derived EVs is to increase the payload of useful factors in EVs through discovery of factors through wound healing and mechanism research [23,24]; there are reports that a calcium-dependent mechanism increases the release of EVs from the cells [25]. However, the important aspect of MSC research is to observe the change in payload inside the MSC and understands its role in disease [21].…”
Section: Introductionmentioning
confidence: 99%